A cura di: Francesco Speciale

${(5x-7y=2),(2x+3/2y=3):}$


 

${(5x-7y=2),(2x+3/2y=3):}$; ${(5x=2+7y),(4x+3y=6):}$;
${(x=(2+7y)/5),(4x+3y=6):}$;
Semplificando e applicando il metodo di sostituzione
${(x=(2+7y)/5),(4(2+7y)/5+3y=6):}$; ${(x=(2+7y)/5),(8/5+(28)/5+3y=6):}$;
${(x=(2+7y)/5),(28y+8+15y=30):}$; ${(x=(2+7y)/5),(43y=22):}$;
${(x=(2+(22)/(43)*7)/5),(y=(22)/(43)):}$; ${(x=(2+(154)/(43))*1/5),(y=(22)/(43)):}$;
${(x=(2/5+(154)/(215))),(y=(22)/(43)):}$; ${(x=(86+770)/(215)),(y=(22)/(43)):}$;
Semplificando
${(x=(48)/(43)),(y=(22)/(43)):}$.